2005
DOI: 10.1002/ccd.20272
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience with the frontrunner coronary catheter: Novel device dedicated to mechanical revascularization of chronic total occlusions

Abstract: The novel device Frontrunner coronary catheter (FCC), dedicated to recanalization of chronic total occlusions (CTOs), relies on blunt microdissections inside the plaque, allowing passage of guidewire through the lesion and adjunctive angioplasty. In order to evaluate efficacy and safety of recanalization using the FCC device, we included patients with de novo or restenotic CTOs in a native coronary artery with prior failure using a guidewire or considered unsuitable for guidewire attempt in which the FCC was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 39 publications
(35 reference statements)
1
21
1
1
Order By: Relevance
“…Guidewire perforation is a well recognized complication of CTO recanalization with an incidence as high as 39% in a previous pilot study of the laser wire [14]. Therefore, our overall complication rate is low and comparable or lower than studies of dedicated guidewires or other new devices [15][16][17]. These preliminary findings need to be confirmed in a large multicenter, prospective trial.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Guidewire perforation is a well recognized complication of CTO recanalization with an incidence as high as 39% in a previous pilot study of the laser wire [14]. Therefore, our overall complication rate is low and comparable or lower than studies of dedicated guidewires or other new devices [15][16][17]. These preliminary findings need to be confirmed in a large multicenter, prospective trial.…”
Section: Discussionsupporting
confidence: 40%
“…This technology allows the guidewire to be redirected prior to causing a dissection or perforation. This system can also generate radiofrequency pulses to facilitate crossing hard fibrotic plaques [15]. Early data have demonstrated a success rate of 50-60% with a low peri-procedural complication rate.…”
Section: Discussionmentioning
confidence: 98%
“…We also found that DSCT could visualize plaques in the CTOs. Despite advances in the development of angioplasty equipment (Saito et al, 2003), such as novel guidewires, as well as various complex techniques (Ng et al, 2003;Orlic et al, 2005), the success rate of PCI in CTOs remains low. Moreover, we found that successful PCI was often obtained in CTOs with a TIMI flow grade 1.…”
Section: Discussionmentioning
confidence: 99%
“…Despite developments in devices and guidewires dedicated for CTO lesion, failure rates are still high, between 20-35% [22,[32][33][34]. The retrograde approach has been introduced to improve recanalization rates.…”
Section: Retrograde Recanalizationmentioning
confidence: 98%